Verosimiglianza storica vs memoria creativa in El prodigioso príncipe transilvano. - Cappelli, Federica (Caietele Echinox, 2023)
In the Spanish theatre of the Golden Age, political propaganda and the consequent need to propose heroes conforming to the prevailing political-religious ideology to the public of corrales de comedia were almost always conditioning the creative process. This is also the case of El prodigioso príncipe transilvano, a historical comedy set at the time of the long Spanish-Turkish conflict (1526-1606) and dedicated to exalting the figure of Sigismund Báthory, in truth one of the most controversial figures in the history of Romanian principalities. This contribution aims at investigating the extent and mechanisms that, in the text, regulate this intersection of historical reliability and creative reworking of a recent past for pro-Spanish and procatholic propaganda purposes.